Analisis Dinding Penahan Tanah Tipe Kantilever Pada Ruas Jalan Kairatu – Hunitetu Kabupaten Seram Bagian Barat - Fernando Jordy Batlolona; Sjafrudin Latar; Penina Istia (Universitas Pahlawan Tuanku Tambusai, 2025)
A soil retaining wall is a construction built to withstand or support soil pressure and other lateral loads with the aim of preventing the soil from unwanted lateral movement. This study aims to determine soil parameters and design soil retaining walls according to standards or theories. The test includes physical and mechanical properties, based on the results of the tests carried out, soil property data is obtained, namely with the type of loamy sandy soil, with a moisture content of 23,68%, the weight of the content with the weight of wet soil volume (yb) is 1.75 gr/cm3 and for the volume of dry soil (yd) is 1.53 kg/cm3, specific gravity is 2.59 Gs, liquid limit (LL) is 39,10%, the plastic limit (PL) was 13,39% and for the plastic index (IP) was 25,71%, the maximum dry volume weight (yd maximum) of the tested soil sample was 1.732 gr/cm3 and the optimum moisture content (W optimum) was 7.66%, as well as the deep shear angle (φ) and cohesion (c) used based on the table of typical values c' and φ (AS 4678,2002), which is used at 25° and 0 KN/m2.